Effectiveness of Multimedia Strategy on Computer Literacy among Elementary School Students of Bangalore Rural District - (:unkn) unknown (University of Jaffna, 2014)
Multimedia strategy is the combination of various digital media types, such as text, animated graphic images, sound, and video, into an integrated multisensory interactive application or presentation to convey content or information. Computer literacy is an understanding of the concepts, terminology and operations that relate to general computer use. It is certain level of expertise and familiarity with computers. It refers to the knowledge and ability to operate a computer and to understand applications. The present study is the Major research project funded by Indian Council of Social Science Research (ICSSR), Ministry of Human Resource Development, Government of India. It aims to find Effectiveness of Multimedia strategy on computer literacy among elementary school students of Bangalore rural district. Data was collected during the academic year 2012-2013 from St.Micheals Elementary school (Private Unaided School) and Bantmaramma Elementary school (government school) of Kanakapura taluk. Total 154 VII standard students from both the schools were formed as control and experimental group. Tools used for the study were Standard Progressive Matrices (Non Intelligence test) developed by Raven and Computer literacy achievement test developed by Dr.T.Pradeep Kumar. Statistical technique employed was Two-Way ANCOVA. Results revealed that Multimedia strategy has a great impact on the achievement of computer literacy among elementary school students, so it is very essential for schools to opt for multimedia technology.
Keywords: Multimedia strategy; Computer literacy; Elementary school students